Understanding the Underlying Islamic Contract of E-Money: The Case of Go-Pay - Hanif Noor Athief, Fauzul; Azizah, Lathifa; Rosyadi, Imron; Hakim, Lukmanul (KnE Social Sciences, 2024)
The rapid development of technology creates a lack of clarity in the Islamic compliance of any new product, including the Go-pay system that serves as a means of payment transactions within Gojek. While researchers already tried to scrutinize Go-Pay under the light of Islamic boundaries, the inconclusive results bring another confusion. This research aims to collect all scholar opinions regarding Go-Pay, and categorize and analyze all the possible underlying Islamic law contracts of Go-Pay. This research is library research, using articles as the data that are extracted from Google Scholar to be analyzed. The results of this study show that the majority of 16 researchers say that Go-Pay payments are more by the Qardh contract. Five researchers found that it is more in line with the Wadi’ah contract, while five others said that it is in line with the Ijarah contract, and one researcher found that the Sharf contract is more appropriate. Keywords: Go-pay, Islam, law, contract, digital money, E-Money, cashless